Combining sites of antibodies with l-alanine and d-alanine peptide specificity and the effect of serum proteolytic activity on their estimation - Schechter, Israel; Schechter, Bilha; Sela, Michael (Biochimica et biophysica acta, 1966)
Antibodies with specificity towards poly- l-alanine and poly- d-alanine were prepared in rabbits by immunization with the respective polyalanyl proteins. From a study of the inhibition of preciption reactions with various alanine peptides it appeared that peptides composed exclusively of the d-isomer were much more efficient inhibitor in the poly- d-alanine immune system than were those composed exclusively of the l-isomer in the poly- l-alanine system. This apparent difference was due to proteolytic activity in rabbi sera. When immunoglobulin G preparations devoid of proteolytic activity were used, no significant differences between the antipodal systems were found. The size of the specific combining region of the antibodies was found to be such as to accommodate a maximum of 3–4 alanine residues, as concluded from the inhibition results. From the extent of inhibition of the stereo-specific antigen-antibody reactions with alanine peptides composed of l and d residues at determined positions, it was concluded that the region of the antigenic determinant furthest removed from the protein carrier is of paramount importance in determining the specificaties of the antibodies formed.